2016
DOI: 10.1021/acs.chemmater.6b00038
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Garnet-Related Li-Ion Conductor Li7–3xGaxLa3Zr2O12: Fast Li-Ion Conduction Caused by a Different Cubic Modification?

Abstract: Li-oxide garnets such as Li7La3Zr2O12 (LLZO) are among the most promising candidates for solid-state electrolytes to be used in next-generation Li-ion batteries. The garnet-structured cubic modification of LLZO, showing space group Ia-3d, has to be stabilized with supervalent cations. LLZO stabilized with Ga3+ shows superior properties compared to LLZO stabilized with similar cations; however, the reason for this behavior is still unknown. In this study, a comprehensive structural characterization of Ga-stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
175
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 192 publications
(209 citation statements)
references
References 54 publications
16
175
1
1
Order By: Relevance
“…Another almost universal feature of R 1 ρ diff in the case of cation-disordered LLZO is the broad relaxation rate peak that spans an extraordinary large temperature range [39,117]. It is definitely the result of a superposition of distinct local and long-range jump processes.…”
Section: Garnet-type Oxides: Cation-stabilized Cubic Llzo and Llzmomentioning
confidence: 99%
See 1 more Smart Citation
“…Another almost universal feature of R 1 ρ diff in the case of cation-disordered LLZO is the broad relaxation rate peak that spans an extraordinary large temperature range [39,117]. It is definitely the result of a superposition of distinct local and long-range jump processes.…”
Section: Garnet-type Oxides: Cation-stabilized Cubic Llzo and Llzmomentioning
confidence: 99%
“…[39,117,118] obtained. Importantly, the low sintering temperatures particularly prevent Li loss during the final annealing step.…”
Section: Phosphates Withmentioning
confidence: 99%
“…35 The Li-ion conductivities of the cubic polymorphs are 2 orders of magnitude higher (σ total ≈ 10 –3 to 10 –4 S·cm –1 at room temperature (RT)) compared to that of the tetragonal polymorph (σ total ≈ 10 –6 S·cm –1 at RT), and the electrochemical properties of the acentric cubic modification seem to be better than the centric one. 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…810 By using a more repulsive cation, i.e., using Ga 3+ instead of Al 3+ , the phase transformation from the centric SG Ia -3 d to the acentric SG I -43 d can be observed. 3 Very recently, some of us have shown that the acentric cubic phase can also be obtained by substituting some of the Li + with Fe 3+ . 5 …”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, single crystal studies by Robben et al and briefly after by Wagner et al Ga-doping is accompanied by a reduction of the LLZO cubic garnet symmetry. 11,12 Buschmann et al reported that Ga substituted LLZO/Li interface showed higher area specific interfacial resistance (ASR) (6000 Ω•cm 2 ) than 0.9 wt% Al substituted LLZO/interface (2800 Ω•cm 2 ). 13 Geiger et al also suggested that a minor concentration of Al in LLZO (0.10 to 0.15 Al per formula unit) as stabilizing agent could compensate the additional charge emergence due to Li + vacancies and then reduce the free energy associated with ordering of the Li sub-lattice in LLZO core symmetry.…”
Section: Introductionmentioning
confidence: 99%